Investigating the Influence of Economic and Socio-Political Openness on Growth - Lena Malešević-Perović; Vladimir Šimić; Vinko Muštra (International Journal of Economic Sciences and Applied Research, 2013)
This paper investigates the influence of international openness on economic growth in a sample of 32 European economies. The usual approach in the literature on the topic is to observe the impact of trade openness on growth. We, however, broaden this standard approach and analyse not only economic aspect of openness but also socio-political aspect. In our empirical analysis we use the TSLS (two stage least squares) estimator, whereby in the first step we use the standard growth regression that includes, among other variables, openness, and in the second step we include different determinants to instrument openness. Our research, in general, shows that openness is an important determinant of growth in a set of investigated countries. Trade openness and financial openness influence growth positively. The influence of institutions on growth is manifested mainly indirectly – through its influence on trade and financial openness.
Keywords: F43; C26; O4; 330; openness; growth; EU; institutions